Hyperkalemia as a cause of undertreatment with mineralcorticoid receptor antagonists for patients with newly onset of heart failure with reduced ejection fraction. (14th October 2021) - Henrysson, J; Thunstrom, E; Fu, M; Basic, C
Abstract: Background: Despite beneficial effects on mortality and morbidity the use of mineralocorticoid receptor antagonists (MRA) in patients with reduced ejection fraction (<40%) (HFrEF) remains poor. Hyperkalemia is assumed as an important cause, but the reported incidence is low and varies hugely. Thus, available data of magnitude of hyperkalemia in real life settings are insufficient to explain why under-utilization of MRA occurred. Aim: To determine the incidence and magnitude of documented hyperkalemia and potential risk of hyperkalemia in patients with HFrEF in a real-world HF population. Methods: Patients aged 18–85 years at the time of the baseline, hospitalized for newly onset of HFrEF between 2016–01–01 and 2019–12–31, were identified retrospectively and consecutively from hospital discharge records, by use of international classification of disease (ICD)-10 codes I50.0-I50.9 as principal diagnosis. Potential higher risk of hyperkalemia was based on an overall assessment of current potassium level, presence of diabetes mellitus and eGFR <30 ml/min at patient level. Results: In total, 3456 patients with HF were identified, 642 (18.6%) were eligible, hospitalized for newly onset of HFrEF (66.8±12.7 years, 68.4% men and EF 29.4% ±6.8%). After six months 336 (52.3%) did not have MRA of which 279 (83%) never received MRAs and 57 (17%) had MRAs discontinued. Among patients on MRA treatment, 306 (14.4%) needed dose reduction. Occurrence of hypertension, ischemic heart disease, diabetes mellitus and renal dysfunction at baseline did not differ between groups with or without MRA. The incidence and magnitude of documented and potentially higher risk of hyperkalemia were assessed both at baseline and as highest potassium within six months after established diagnosis. Among patients without MRA after six months, at baseline only 3 (0.9%) patients had documented S/P-K ≥6 mmol/L, 7 (2.1%) patients had S/P-K 5.5–5.9 mmol/L and 26 (7.7%) patients had S/P-K 4.8–5.4 mmol/L. Moreover, 12.4% had potentially high risk of hyperkalemia at baseline. During the six-month follow up after initiation of HF therapy, 15 (4.5%) patients had documented hyperkalemia with S/P-K ≥6 mmol/L, 23 (6.8%) patients had S/P-K 5.4–5.9 mmol/L, and 123 (36.6%) patients had S/P-K 4.8–5.4 mmol/L during at least one occasion. Besides, 13.4% had potentially high risk of hyperkalemia. Hyperkalemia occurred frequently (40.4% vs 36.4%) in patients with discontinuation and dose reduction of MRA. Figure 1 presents the distribution of patients with risk of or documented hyperkalemia in the group without MRA. Conclusions: Hyperkalemia was the most common cause for both discontinuation and dose reduction of MRA. Hyperkalemia was also increased significantly from baseline and during subsequent up-titration, with 4.6-fold increased risk for borderline hyperkalemia (S/P-K 4.8–5.4). This might explain why physicians refrain from prescribing MRAs to patients with HFrEF. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Vifor Pharma